1993
DOI: 10.1088/0268-1242/8/9/008
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo calculations of base transit time in bipolar transistors

Abstract: Previous analytical treatments of low-field electron transpolt in the base of bipolar transistors have all made the implicit assumption that the velocity distributions are Gaussian. Using material and scattering parameters appropriate to GaAs and a simple model for the transistor base in which the wllector is replaced by a step potential, we have found that near the collector these distributions are distorted, leading to a diffusion velocity exceeding the thermal velocity. We also investigated the effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, because the yellow light emitting from the phosphor YAG:Ce lacks sufficient red emission, this white light has a low color rendering index Ra (CRI), in the 60-70 range. As may be excepted, red enhanced YAG:Ce or combine a small amount of red phosphor with YAG:Ce could improve the CRI to the acceptable range (Ra > 80) and increased the light conversion [1][2][3][4][5][6][7][8][9]. * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…However, because the yellow light emitting from the phosphor YAG:Ce lacks sufficient red emission, this white light has a low color rendering index Ra (CRI), in the 60-70 range. As may be excepted, red enhanced YAG:Ce or combine a small amount of red phosphor with YAG:Ce could improve the CRI to the acceptable range (Ra > 80) and increased the light conversion [1][2][3][4][5][6][7][8][9]. * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…This would result in a filtering effect and would affect the electron distribution injected into the base. It has already been demonstrated by Mills et al [40] that the form of the injected distribution at the edge of a GaAs base can influence the transit times in short bases, and it is possible that similar effects might also occur here.…”
Section: Discussionmentioning
confidence: 68%
“…Work by Mills et al [17] suggested that the Gaussian velocity distribution injected into the base region in these types of simulation does not accurately model the injected distribution in a real transistor, leading to higher base transit times, most significantly in short bases (less than 500 Å). This is because the injected distribution does not have a sufficient distance in which to relax to the correct equilibrium distribution before it encounters the base-collector boundary.…”
Section: Discussionmentioning
confidence: 99%